2004
DOI: 10.1002/ajp.20000
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation and consolation in captive bonobos (Pan paniscus)

Abstract: Although reconciliation in bonobos (Pan paniscus) has previously been described, it has not been analyzed heretofore by the postconflict (PC) match-control (MC) method. Furthermore, although reconciliation has been investigated before in this species, consolation has not. In this study we analyzed agonistic and affiliative contacts in all sex-class combinations to clarify and reevaluate the occurrence of reconciliation in bonobos via the PC-MC method. We also investigated the occurrence of consolation by analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
118
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 46 publications
(47 reference statements)
9
118
2
Order By: Relevance
“…Their avoidant behavior was not necessarily maladaptive, therefore. However, it is the mother-reared juveniles that showed the full spectrum of social skills and socio-emotional responses typical of bonobos (16,40,44). They showed a tight interconnection between the regulation of their own emotions, their reaction to the emotions of others, and how they navigated their social world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their avoidant behavior was not necessarily maladaptive, therefore. However, it is the mother-reared juveniles that showed the full spectrum of social skills and socio-emotional responses typical of bonobos (16,40,44). They showed a tight interconnection between the regulation of their own emotions, their reaction to the emotions of others, and how they navigated their social world.…”
Section: Discussionmentioning
confidence: 99%
“…Consolation is defined as spontaneous contact comfort aimed at distressed parties by means of touching, stroking, embracing, and kissing (15) (Fig. 1), a behavior well-known of both children and apes (4)(5)(6)(12)(13)(14)(15)(16). In human children, consolation behavior appears already in the first year of life (10,17), suggesting that although the cognitive component of empathy increases across development, it is no prerequisite for expressions of concern.…”
mentioning
confidence: 99%
“…Many studies suffer from small sample sizes. For example, Palagi et al (2004) found, in a captive bonobo group, male-female and femalefemale dyads with close relationships reconciled more conflicts than those with distant relationships. However, their study group had only 5 members, which limited analysis at the dyad level and made any conclusions tentative.…”
Section: Testing the Vrhmentioning
confidence: 99%
“…7,10 The majority of research on post-conflict behavior has focused on reconciliation, the affiliative post-conflict interaction between former opponents, 11,12 but important post-conflict interactions may also occur between the opponents and bystanders uninvolved in the previous conflict. 13,14 In particular, a number of recent studies have demonstrated the phenomenon of post-conflict affiliation directed from a bystander to the recipient of aggression in a variety of species from primates [15][16][17][18][19][20][21][22][23][24][25] to dogs 26 and rooks. 27 This review focuses on bystander to recipient interactions and examines the variations in their patterns, which are consistent with a number of different functional explanations.…”
Section: Introductionmentioning
confidence: 99%